The Biogeochemical Sulfur Cycle of Marine Sediments - Jørgensen, Bo Barker; Findlay, Alyssa J.; Pellerin, André (Frontiers in Microbiology, 2019)
Dissimilatory microbial sulfate reduction to sulfide is the predominant terminal pathway of organic matter mineralization in the seabed. Chemical or microbial oxidation of the produced sulfide establishes a complex network of pathways in the sulfur cycle, leading to intermediate sulfur species and ultimately back to sulfate. The intermediates include elemental sulfur, polysulfides, thiosulfate and sulfite, which are all substrates for further microbial oxidation, reduction or disproportionation. New microbiological discoveries, such as long-distance electron transfer through sulfide oxidizing cable bacteria, add to the complexity. Isotope exchange reactions play an important role for the stable isotope geochemistry and for the experimental study of sulfur transformations using radiotracers. Microbially catalyzed processes are partly reversible whereby the back-reaction affects our interpretation of radiotracer experiments and provides a mechanism for isotope fractionation. We here review the progress and current status in our understanding of the sulfur cycle in the seabed with respect to its microbial physiology, biogeochemistry and isotope geochemistry.